Cytotoxicity and Nitric Oxide Production Inhibitory Activities of Compounds Isolated from the Plant Pathogenic Fungus Curvularia sp. - Virayu Suthiphasilp; Achara Raksat; Tharakorn Maneerat; Sarinya Hadsadee; Siriporn Jungsuttiwong; Stephen G. Pyne; Putarak Chomnunti; Wuttichai Jaidee; Rawiwan Charoensup; Surat Laphookhieo (Journal of Fungi, 2021)
Chemical investigation of the mycelia of the pathogenic fungus Curvularia sp. which was isolated from a leaf of Dactyloctenium aegyptium (crowfoot grass), resulted in the isolation of a new compound, curvulariahawadride (5), along with five known compounds (1–4, and 6). Their structures were determined on the basis of spectroscopic data, including 1D and 2D NMR and HRESIMS. The absolute configuration of 5 was established from experimental and calculated electronic circular dichroism (ECD). Compounds 1, 3, and 5 showed nitric oxide (NO) production inhibitory activity with IC50 values of 53.7, 32.8, and 12.8 µM, respectively. Compounds 2 and 4 showed significant cytotoxicity against lung cancer A549, colorectal cancer SW480, and leukemic K562 cells with an IC50 ranging value of 11.73 to 17.59 µM.